Education on the Importance of Maintaining the Cleanliness of the Riverbank Environment to Prevent Potential Flooding Due to Water Overflow - Muhammad Ilzam Maulana; Putri, Inge Wiliandani Setya; Wardoyo, Arik Aguk; Saharani, Firanti Nur; Putri, Revita Juliane (International Assulta of Research and Engagement (IARE), 2024)
Environmental cleanliness is a basic thing that must be considered. Unfortunately, it is not easy to create a clean and comfortable environment. Many people still ignore this problem. This service aims to educate about the importance of maintaining the cleanliness of the riverbank environment to prevent potential flooding. This service method uses Participatory Rural Appraisal (PRA), with a service team by students of Mathematics Education, FKIP, University of Jember, together with the community of Tegal Gede Village, Jember, which was carried out in 2024. The results show that service through this social service has motivated the community to care more about the environment and minimize the occurrence of disasters. So, this social service activity has provided the community with enthusiasm and motivation to care more about the surrounding environment.